2016
DOI: 10.1039/c5tx00265f
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal caffeine exposure-induced adrenal developmental abnormality in male offspring rats and its possible intrauterine programming mechanisms

Abstract: Glucocorticoid (GC) is a major factor for fetal tissue maturation and fate decision after birth. We previously demonstrated that prenatal caffeine exposure (PCE) suppressed fetal adrenal steroidogenesis and resulted in adrenal dysplasia. However, whether these changes play a role until adulthood and its intrauterine programming mechanisms remain unknown. In the present study, a rat model of intrauterine growth retardation (IUGR) was established by PCE, male fetuses and adult offspring were sacrificed at postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
3
11
1
Order By: Relevance
“…The zona fasciculata is most frequently affected by noxious compounds [29], and chemically-induced toxicity causes impaired steroidogenesis, leading to excess steroid precursors and cytoplasmic vacuolation in the adrenal cortical cells of the zona fasciculata [29]. Similarly, we observed histological distortion of the adrenal cortex including cloudy swellings and some vacuolation within the cells of the zona fasciculata, dilation of some blood sinusoids, and more dilated intercellular spaces in the cortex in the caffeine-fed groups, particularly the females (Figure 4A) (Table 1), consistent with previous data on caffeine exposure of adult and fetal animals [8,9,10]. During puberty, there is marked expansion of the zona fasciculata [26], which constitutes the main bulk of the adrenal cortex.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The zona fasciculata is most frequently affected by noxious compounds [29], and chemically-induced toxicity causes impaired steroidogenesis, leading to excess steroid precursors and cytoplasmic vacuolation in the adrenal cortical cells of the zona fasciculata [29]. Similarly, we observed histological distortion of the adrenal cortex including cloudy swellings and some vacuolation within the cells of the zona fasciculata, dilation of some blood sinusoids, and more dilated intercellular spaces in the cortex in the caffeine-fed groups, particularly the females (Figure 4A) (Table 1), consistent with previous data on caffeine exposure of adult and fetal animals [8,9,10]. During puberty, there is marked expansion of the zona fasciculata [26], which constitutes the main bulk of the adrenal cortex.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, prenatal caffeine exposure has been reported to reduce adrenal cortical area by half in male rat offspring [9]. However, we observed no difference in adrenal cortical or medullary area between caffeine-fed and control males (Figure 3), whereas in the caffeine-fed females, cortical and medullary areas increased in spite of the reduced absolute weights of the adrenals.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In our previous researches, we have demonstrated that PEE could induce fetal over-exposure to maternal glucocorticoids in utero (26, 55, 56), which further increased the GR expression [e.g., hippocampus (56) and adrenals (26)] and decreased IGF1 expression [e.g., adrenals (26), and liver (28)] of multiple fetal organs, and thus resulted in their developmental programming alterations. In addition, in other IUGR models induced by prenatal exposure to xenobiotics [such caffeine (57), nicotine (58)], we have also found the fetal over-exposure to maternal glucocorticoids, and the alterations of GR expression in multiple fetal organs, accompanied with related developmental programming changes. In the present study, we found that the contents of pancreatic insulin and proinsulin were lower, and the expression levels of INS1, INS2 and ISL1 mRNA were decreased in the PEE group, furthermore, the GR mRNA expression level was increased but the expression level of IGF1 mRNA was decreased.…”
Section: Discussionmentioning
confidence: 66%